Pembentukan Karakter Kemandirian Santri pada Madrasah Berbasis Pesantren di Madrasah Aliyah Al-Hamidiyah Jawa Barat - Saimroh Saimroh (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2020)
Among other problems, adolescents are caused by a lack of independence in living their lives. However, for students who live in a pesantren environment, independence has become a life requirement. Learning activities at Madrasah Aliyah Al-Hamidiyah, Depok, West Java which are based on Islamic boarding schools, encourage selfreliance learning for their students. This study aims to describe students' level of independence and the efforts made in establishing the independence of students at Madrasah Aliyah Al-Hamidiyah. The research method uses a mix-method approach, in which data collection is carried out using a questionnaire and is supported by observation, interview, and document study methods. The research data were analyzed using qualitative descriptive techniques. The study results found that in general the independence index of students at Madrasah Aliyah Al Hamidiyah was in the high category. The achievement of the emotional autonomy index of the santri is in the high category, behavioral autonomy is in the high category, and value autonomy is in the very high category. Efforts to form independence are carried out by integration through curriculum, self-development, habituation, or culture. The obstacles faced in the effort to build character come from internal and external factors. The results of this study recommend the need for the Ministry of Religion and Islamic educational institutions to develop a policy formula for strengthening character education that is more creative, innovative and has distinctive characteristics of Islamic education.